MEWUJUDKAN KELUARGA SAKINAH BAGI PASANGAN DISABILITAS TUNA DAKSA: TINJAUAN PERSPEKTIF MAQASHID SYARI'AH - Maryanto, Budhi Tri; Syamsuddin, S (AL HUKMU: Journal of Islamic Law and Economics, 2025)
a sakinah family for person with disabilities represents an ideal form of household life build on tranquility, affection, and compassion despite physical limitations. In the context of disability, a sakinah family reflects the couple's ability to understand, support, and maintain commitment to one another even amidst social and economic challengers. This study aims to analyze how persons with physical disabilities (tuna daksa) form sakinah families from the perspective of Maqashid Syariah. Using s qualitative approach with a case study method. Data were collected through in depth interviews, observations, and documentation involving five disabled couples in Tugu village, Cawas District, Klaten Regency. The result reveal that disabled couples can establish harmonious families by applying Islamic principles such as fulfilling basic needs, maintaining dignity, and ensuring children's education. The principles of values such as hifz al-din (protection of religion), hifz al-nafs (protection of life), hifz al-'aql (protection of intellect), hifz al-nasl (protection of lineage), hifz al-mal (protection of wealth). Challenges they face include social stigma, limited access to facilities, and uneven distribution of social assistance. This study highlights the importance of environmental support and inclusive policies in achieving the ideal sakinah family for persons with disabilities.